Early Detection of Magnaporthe oryzae-Infected Barley Leaves and Lesion Visualization Based on Hyperspectral Imaging - Zhou, Rui-Qing; Jin, Juan-Juan; Li, Qing-Mian; Su, Zhen-Zhu; Yu, Xin-Jie; Tang, Yu; Luo, Shao-Ming; He, Yong; Li, Xiao-Li (Frontiers in Plant Science, 2019)
Early detection of foliar diseases is vital to the management of plant disease, since these pathogens hinder crop productivity worldwide. This research applied hyperspectral imaging (HSI) technology to early detection of Magnaporthe oryzae-infected barley leaves at four consecutive infection periods. The averaged spectra were used to identify the infection periods of the samples. Additionally, principal component analysis (PCA), spectral unmixing analysis and spectral angle mapping (SAM) were adopted to locate the lesion sites. The results indicated that linear discriminant analysis (LDA) coupled with competitive adaptive reweighted sampling (CARS) achieved over 98% classification accuracies and successfully identified the infected samples 24 hours after inoculation. Importantly, spectral unmixing analysis was able to reveal the lesion regions within 24 hours after inoculation, and the resulting visualization of host-pathogen interactions was interpretable. Therefore, HSI combined with analysis by those methods would be a promising tool for both early infection period identification and lesion visualization, which would greatly improve plant disease management.